Penerapan Konsep A.B.L.E. Pada Ruang Terapi Anak Berkebutuhan Khusus Cerebral Palsy - Andreas Dwiputro Handoyo; Widyanesti Liritantri; Mutiara Dhya Ulhaq Pramesi; Allicia Sandra Meirissa (ARSITEKTURA, 2020)
Cerebral Palsy is a condition characterized by poor muscle control, stiffness, paralysis, to other nerve disorders. These children are at the highest level of priority among children with special needs. Helping children with Cerebral Palsy can be realized through the design of a special therapy centre for children with Cerebral Palsy.  The design of this therapy centre will be specified in the design concept of the play therapy room because in this case, the playground works as well as therapeutic method for children. This study was conducted using qualitative descriptive analytical methods in Risantya facility which applies play as a therapeutic approach. The observation focused on the activities of the children in the playground. It was found that four factors play an important role in the therapy area. A.B.L.E. has meaning, namely A for Attractive Colours, B for Bump, Bruise, and Pain-Free, L for Low Physical Effort, and E for Engaged positively with movement. The concept is described to therapy centre, especially in the play therapy room, where this concept aims to provide a sense of ease, safety, and comfort to children when doing activities.